The α5 Nicotinic Acetylcholine Receptor Subunit Differentially Modulates α4β2* and α3β4* Receptors - Scholze, Petra; Huck, Sigismund (Frontiers in Synaptic Neuroscience, 2020)
Nicotine, the principal reinforcing compound in tobacco, acts in the brain by activating neuronal nicotinic acetylcholine receptors (nAChRs). This review summarizes our current knowledge regarding how the α5 accessory nAChR subunit, encoded by the CHRNA5 gene, differentially modulates α4β2* and α3β4* receptors at the cellular level. Genome-wide association studies have linked a gene cluster in chromosomal region 15q25 to increased susceptibility to nicotine addiction, lung cancer, chronic obstructive pulmonary disease, and peripheral arterial disease. Interestingly, this gene cluster contains a nonsynonymous single-nucleotide polymorphism (SNP) in the human CHRNA5 gene, causing an aspartic acid (D) to asparagine (N) substitution at amino acid position 398 in the α5 nAChR subunit. Although other SNPs have been associated with tobacco smoking behavior, efforts have focused predominantly on the D398 and N398 variants in the α5 subunit. In recent years, significant progress has been made toward understanding the role that the α5 nAChR subunit—and the role of the D398 and N398 variants—plays on nAChR function at the cellular level. These insights stem primarily from a wide range of experimental models, including receptors expressed heterologously in Xenopus oocytes, various cell lines, and neurons derived from human induced pluripotent stem cells (iPSCs), as well as endogenous receptors in genetically engineered mice and—more recently—rats. Despite providing a wealth of available data, however, these studies have yielded conflicting results, and our understanding of the modulatory role that the α5 subunit plays remains incomplete. Here, we review these reports and the various techniques used for expression and analysis in order to examine how the α5 subunit modulates key functions in α4β2* and α3β4* receptors, including receptor trafficking, sensitivity, efficacy, and desensitization. In addition, we highlight the strikingly different role that the α5 subunit plays in Ca2+ signaling between α4β2* and α3β4* receptors, and we discuss whether the N398 α5 subunit variant can partially replace the D398 variant.